2005
DOI: 10.1186/bf03352569
|View full text |Cite
|
Sign up to set email alerts
|

The 2004 sequence of triggered earthquakes off the Kii peninsula, Japan

Abstract: We examine the spatial and temporal relationships of the sequence of strong earthquakes that occurred off the Kii Peninsula, Japan, on 5 September 2004. The first event (Mj 7.1) occurred at 10:07:08 (UTC) on a northward dipping plane within the subducting Philippine Sea plate. From 10:16 to 14:47 the seismicity shows a group of earthquakes (Mj 3.2 to 4.8) 35 km to the east which are regarded as foreshocks to the second large earthquake. At 14:57:17, a Mw 6.1 strike-slip event occurred on a northwest trending p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 12 publications
1
19
1
Order By: Relevance
“…We therefore propose the existence of a fault in the oceanic lithosphere. A fault such as this is consistent with the mechanism of the fault that generated the mainshock of the 2004 earthquakes, which also dips to the south (e.g., Hashimoto et al, 2005;Park and Mori, 2005;Bai et al, 2007). Seismic activity farther down-dip along the subducting PHS is very much lower.…”
Section: Seismic Activity Along the Nankai Troughmentioning
confidence: 59%
See 1 more Smart Citation
“…We therefore propose the existence of a fault in the oceanic lithosphere. A fault such as this is consistent with the mechanism of the fault that generated the mainshock of the 2004 earthquakes, which also dips to the south (e.g., Hashimoto et al, 2005;Park and Mori, 2005;Bai et al, 2007). Seismic activity farther down-dip along the subducting PHS is very much lower.…”
Section: Seismic Activity Along the Nankai Troughmentioning
confidence: 59%
“…12) and extend to very shallow depths in the oceanic crust. Although the fault that generated the foreshock of the 2004 event dips to the north (e.g., Park and Mori, 2005;Bai et al, 2007), the hypocentral plane in Figure 12 dips to the northeast and does not therefore represent that fault. In this region, Tsuji et al (2013) identified northeast-dipping intraoceanic thrusts that are consistent with the hypocenter distribution we have defined.…”
Section: Seismic Activity Along the Nankai Troughmentioning
confidence: 96%
“…8(a)). The M w =7.5 mainshock occurred about 5 h after the foreshock on a multiple faulting with primarily two different fault planes: a northwest-tending strike-slip fault plane and a south-dipping reverse fault plane (Miyoshi and Ishibashi, 2005;Park and Mori, 2005;Satake et al, 2005;Yagi, 2005). After the mainshock, earthquakes extended in both the northwest and southwest directions from the location of the mainshock (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There have been some similar examples in regions of triggered seismicity where smaller “foreshocks” led to a larger triggered earthquake within hours to days. These include the M6.5 Big Bear event following the M7.4 Landers earthquake [ King et al , 1994], the M5.5 event following the M6.6 2000 western Tottori, Japan, earthquake [ Ohmi et al , 2002], the M7.4 event following the M7.1 2004 Kii Peninsula, Japan, earthquake [ Park and Mori , 2005]. …”
Section: Discussionmentioning
confidence: 99%